Peningkatan Pengetahuan Kesehatan Reproduksi Remaja Dalam Upaya Pencegahan Pernikahan Usia Anak di Yayasan Assulamy, Desa Langko, Lombok Barat - Claudea, Noralia; Safitri, Ratu Shila; Fabian, Muhammad Fahier; Karim, L.M Fathul; Rizki, Khairur; Makhroja, Mega Nisfa (Jurnal Masyarakat Indonesia (Jumas), 2025)
This service was carried out for Langkah Muda, students of Mataram University which is located at Jalan Majapahit-Mataram NTB. This community service activity was carried out on Saturday, 24 August 2024. The theme for this community service was Sex Educations for students at Yayasan Assulamy. Thru this education, students will learn about their bodies, sexual health and relationships. It also promotes healthy relationships by discussing consent and respect. As the nation's generation and hope, students' knowledge about sex education needs to be improved in order to make child marriage number in NTB decrease. The service method is carried out in namely the lecture of Perkumpulan Keluarga Berencana Indonesia Kota Mataram. The results of this service activity are expected to prepares students to make informed and healthy choices about their sexuality.